2014
DOI: 10.1016/j.crohns.2014.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient and physician views on the quality of care in inflammatory bowel disease: Results from SOLUTION-1, a prospective IG-IBD study

Abstract: Healthcare was rated as satisfactory overall for Italian patients and physicians. The physicians underestimate their competence and consider the cost of medical management unsatisfactory. The patients are more critical regarding the continuity of care and information. Country-specific data on QoC allow local governments to allocate resources more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…Other studies have demonstrated that because of the complexity, impact on the patient's life and lifelong nature of IBD, it should ideally be managed by a multidisciplinary team characterised by continuity of care (Bortoli et al . , Calvet et al . , Louis et al .…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that because of the complexity, impact on the patient's life and lifelong nature of IBD, it should ideally be managed by a multidisciplinary team characterised by continuity of care (Bortoli et al . , Calvet et al . , Louis et al .…”
Section: Discussionmentioning
confidence: 99%
“…This is not the case in our population, as the Italian IBD patients are in the best conditions to adhere to the therapy as they do not bear most of the economic burden of the disease and receive a high-quality assistance. As a matter of fact, Italian IBD patients report to be overall satisfied with the quality of the healthcare assured [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in younger patients, poor HRQoL is often associated with negative illness perception, which is the subjective meaning that patients give to their disease [13]. Another important aspect is the patients' satisfaction with treatment and trust in their healthcare providers, both factors that could affect compliance with the therapy and follow-up visit program and represent a challenging issue for gastroenterologists [14].…”
Section: Introductionmentioning
confidence: 99%